Building an Islamic Development Paradigm: Criticism of Gerard Clarke and the Relevance of SDGs in Contemporary Da'wah - Aslichan Aslichan; Taufiq Rahman; Asep Sahid Gatara; Tata Sukayat (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
This article re-examines the dominant secular-liberal paradigm in international development through a critical engagement with Gerard Clarke’s analysis in “Religion and International Development” (2009). While Clarke acknowledges the expanding role of faith-based organizations in development practice, his framework remains largely instrumental and does not sufficiently conceptualize religious and spiritual values as an alternative epistemological foundation for development. Employing a qualitative methodology based on critical textual analysis and comparative examination of development policies and practices, this study explores how key Islamic principles, including Tawhid, Islah, and Maqashid Syariah, inform normative understandings of sustainable and ethical development. Drawing on selected cases from Malaysia, Bangladesh, and Indonesia, the analysis highlights the potential contribution of Islamic social finance instruments, such as zakat, waqf, and sharia-compliant microfinance, to inclusive development outcomes. The findings suggest that, when effectively institutionalized, these instruments can support social justice, women’s economic participation, and environmental responsibility. This study contributes to development studies by extending faith-based development debates beyond instrumental approaches and offers policy-relevant insights for integrating Islamic ethical frameworks into contemporary development strategies